Effectiveness and Safety of Cystic Fibrosis Transmembrane Conductance Regulator Modulators in Children With Cystic Fibrosis: A Meta-Analysis - Li, Qiyu; Liu, Siyuan; Ma, Xuemei; Yu, Jiaping (Frontiers in Pediatrics, 2022)
Abstract: Background and aim: Cystic fibrosis (CF) is a genetic disease which is difficult to treat and caused by dysfunction of the cystic fibrosis transmembrane conductance regulator (CFTR) protein. Small molecules have been used to treat the symptom caused by CFTR mutations by restoring CFTR protein function. However, the data on children with CF are scarce. This meta-analysis aimed to evaluate the effectiveness and safety of this therapy in children diagnosed with CF. Methods: Relevant studies were identified through searching medical databases before April 1, 2022. The primary outcomes of ppFEV1, lung clearance index2.5 (LCI2.5), sweat chloride concentration (SwCI), and Cystic Fibrosis Questionnaire-Revised (CFQ-R) score were pooled and analyzed. The secondary outcomes were nutritional status (weight, BMI, stature, and their z-score) and adverse events under therapy. Results:A total of twelve studies were included. Compared with the placebo group, the pooled outcome of the ppFEV1, LCI2.5, SwCI, and CFQ-R score were improved by 7.91 [95% confidence interval (CI), 3.71–12.12), –1.00 (95% CI, –1.38 to –0.63), –35.22 (95% CI, –55.51 to –14.92), and 4.45 (95% CI, 2.31–6.59), respectively]. Compared with the placebo group, the pooled result of the change in weight was improved by 1.53 (95% CI, 0.42–2.63). All the aforementioned results were also improved in single-arm studies. No clear differences in adverse events were found between CFTR modulator therapy and the placebo group. Conclusion: CFTR modulators could improve multiaspect function in children with CF and result in comparable adverse events.